Market-Indexed Executive Compensation: Strictly for the Young - Gerald T. Garvey; Todd T. Milbourn (Claremont McKenna College, Department of Economics, 2001)
Academics have long argued that incentive contracts for executives should be indexed to remove the influence of exogenous market factors. Little evidence has been found that firms engage in such practices, also termed 'relative performance evaluation'. We argue that firms may not gainmuch by removing market risks from executive compensation because (i) the market provides compensation for bearing systematic risk via the market risk premium and therefore the executive desires positive exposure to such risks, and (ii) the executive can, in principle, adjust her personal portfolio to o.set any unwanted market risk imposed by her compensation contract. A testable implication is that stock-based performance incentives will be weaker when idiosyncratic risks are large but that market risks will have little e.ect. The data tend to support this hypothesis. In the full sample of CEO compensation from ExecuComp, stock-based incentives are strictly decreasing in firm-specific risk. Market-specific risks, however, are insignificantly related to incentives. The story changes somewhat when we distinguish between younger and older CEOs. Our theory is arguably less applicable to younger CEOs who have more non-tradeable exposure to systematic risk through their human capital. Consistent with this argument, we find that market risks have a negative e.ect on stock-based incentive pay for younger CEOs, while they don't for older CEOs. This in turn implies that the traditional argument for indexation is indeed valid for younger CEOs, and we find some evidence in favor of this proposition. Specifically, we find evidence of indexation for younger but not for older CEOs. Even for younger CEOs, however, the e.ect is far too weak to remove the e.ects of market risk. This is consistent with our finding that market risk reduces pay-performance for young CEOs, but leaves the question of why there is not more indexing for such executives.
Keywords: 330